Fungicida a base de la semilla de aguacate (2024)
This research project focuses on the extraction of substances from Hass avocado seeds (Persea Americana). When choosing the seeds, the maturity of the fruit was taken into account and the presence of polyphenols was sought to be determined. The fruit, widely grown in Colombia, offers an important valuation opportunity because its seed residues represent between 15 and 18 percent of the fruit. To carry out this study, an experimental methodological design was proposed, applying an extraction method and an appropriate solvent together with laboratory tests. Cold extraction was chosen as the method, where distilled water and 90% ethanol were used as solvents. The resulting extract was positive for the final concentration after passing through the rotary evaporator.